Zirconia sintered body and method for manufacturing the same
Patent Information
- Application Number
- JP2026062006
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-04-04
- Filing Date
- 2026-04-03
- Publication Date
- 2026-10-16
AI Technical Summary
【0009】 本開示では、複合プレートとすることなく、荷重をかけた時の変形の弾性率が低いジルコニア焼結体及びその製造方法の少なくともいずれかを提供することができる。
Smart Images

Figure 2026169211000004 
Figure 2026169211000005 
Figure 2026169211000006
Abstract
Description
[Technical Field]
[0001] This disclosure relates to a zirconia sintered body and a method for manufacturing the same. [Background technology]
[0002] In addition to conventional applications requiring strength, such as grinding media and structural materials, zirconia sintered bodies are being considered for decorative applications, such as decorative parts for watches, portable electronic devices, automobiles, and home appliances. For decorative applications, zirconia sintered bodies need to have reduced brittleness; that is, they need to be flexible with low rigidity and a low modulus of elasticity when deformed under load.
[0003] For example, Patent Document 1 discloses that a composite plate made by bonding glass fiber reinforced resin to a zirconia-alumina composite material exhibits a biaxial bending test in which the modulus of elasticity when a load is applied is 40 GPa, which is lower than the modulus of elasticity of zirconia (250 GPa). [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 2014-113726 [Overview of the Initiative] [Problems that the invention aims to solve]
[0005] However, the decrease in the elastic modulus of this composite plate is due to the glass fiber reinforced resin bonded to the zirconia-alumina composite material. While composite plates with such resins bonded to them have lower rigidity due to the decrease in elastic modulus, there is room for improvement in the strength of the resin portion, which limits their application to decorative purposes.
[0006] The purpose of this disclosure is to provide at least one of the following: a zirconia sintered body with a low modulus of elasticity when a load is applied, without the need for a composite plate; and a method for manufacturing the same. [Means for solving the problem]
[0007] This disclosure details the relationship between the elastic modulus of deformation and strain in a small interval, specifically the differential coefficient obtained by the difference approximation of the stress-strain diagram of a zirconia sintered body using the three-point bending test method. As a result, we found a low-rigidity behavior in which the elastic modulus of deformation decreases with increasing strain, and confirmed that zirconia sintered bodies exhibiting this behavior cannot be produced from conventional raw materials. Therefore, we found that by discovering a different sintering mechanism and suitable raw materials, it is possible to realize a zirconia sintered body with low rigidity, i.e., flexibility.
[0008] In other words, the present invention is as described in the claims, and the gist of this disclosure is as follows: [1] Containing one or more stabilizing elements selected from the group consisting of yttrium, calcium, magnesium, and cerium, The surface crystalline phase includes at least monoclinic and tetragonal phases, and The deformation modulus at the fracture point, as shown in the deformation modulus (Δσ / Δε)-ε diagram obtained from the stress (σ)-strain (ε) relationship in a three-point bending test, is 130 GPa or less. Zirconia sintered body. [2] The zirconia sintered body according to [1] above, wherein the crystalline phase of the surface includes rhombohedral crystals. [3] When converted to oxides, the yttrium content is 0.9 mol% or more and 2.0 mol% or less, the calcium content is 3.0 mol% or more and 6.0 mol% or less, the magnesium content is 1.0 mol% or more and 6.0 mol% or less, and / or the cerium content is 4.0 mol% or more and 8.0 mol% or less, and The monoclinic ratio of the surface is 16% or more and 50% or less. The zirconia sintered body described in [1] or [2] above. [4] The strain at the bending point is 0.003 or greater and less than or equal to the fracture point, The deformation modulus and strain at a point where the strain is above the bending point and below the fracture point have a linear relationship, and furthermore, The slope of the line is -10000 GPa or less. A zirconia sintered body as described in any one of the above [1] to [3]. [5] A zirconia sintered body according to any one of [1] to [4] above, comprising at least one of alumina and silica as additive components. [6] The zirconia sintered body according to [5] above, wherein the content of the additive component is 5.0% by mass or less. [7] BET specific surface area is 40m 2 / g or more 100m 2 A molded body made of zirconia powder containing one or more stabilizing elements selected from the group consisting of yttrium, calcium, magnesium, and cerium, with a measured density of 5.65 g / cm³, was sintered. 3 More than 5.90g / cm 3 To obtain the following preliminary zirconia sintered bodies, and, Pressurizing the pre-sintered zirconia body A method for producing a zirconia sintered body according to any one of the above [1] to [6], including the above. [8] A component comprising a zirconia sintered body as described in any one of the above [1] to [6]. [Effects of the Invention]
[0009] This disclosure provides at least one of the following: a zirconia sintered body with a low modulus of elasticity when a load is applied, without the need for a composite plate; and a method for manufacturing the same. [Brief explanation of the drawing]
[0010] [Figure 1] Figure 1 shows an example of a deformation modulus-strain diagram (comparison of Example 1 and Comparative Example 1). [Figure 2] Figure 2 shows an example of a linear approximation line (Δσ / Δε=αε+β) of the deformation modulus-strain plot determined by the least squares method (comparison of Example 1 and Comparative Example 1). [Figure 3]Figure 3 shows an example of the volume-based (a) crystallite size distribution and (b) cumulative crystallite size distribution determined by the diffraction lines of monoclinic -111 reflection (comparison of Example 1 and Comparative Example 1). [Modes for carrying out the invention]
[0011] The following description illustrates an example of this disclosure. This disclosure includes any combination of the configurations and numerical values disclosed herein, as well as any combination of the upper and lower limits disclosed herein.
[0012] The "three-point bending test" is a test conducted in accordance with JIS R 1601.
[0013] "Stress" (hereinafter also referred to as "σ") is the value obtained by substituting the load value measured from the three-point bending test into the following equation (1). σ = 3PL / (2bh) 2 ) (1)
[0014] In equation (1), σ is stress (MPa), P is the load (N), L is the distance between the support points (mm). b is the width of the test specimen (mm), h is the thickness of the test specimen (mm). That is the case.
[0015] "Strain" (hereinafter also referred to as "ε") is the value obtained by substituting the deflection value measured from the three-point bending test into the following equation (2). ε = 6hs / L 2 (2)
[0016] In equation (2), ε is distorted (dimensionless), s is the deflection (mm), h and L are the same as in equation (1). That is the case.
[0017] The "breaking point" refers to the value at which the stress reaches its maximum. When the strain exceeds the breaking point, the stress sharply drops as the test piece breaks.
[0018] The aforementioned load and deflection are values measured by a method conforming to JIS R1601, and may be measured under the following conditions using a general autograph (for example, product name: AGS-10kNX, manufactured by Shimadzu Corporation, analysis software: TRAPEZIUM LITE X, manufactured by Shimadzu Corporation).
[0019] Autograph Distance between supporting points: 30±0.1 mm Crosshead speed: 0.5 mm / min Sampling acquisition interval: 0.01 seconds Test piece size Test piece width: 4.00±0.1 mm Test piece thickness: 3.00±0.1 mm Test piece length: 36 mm or more and less than 45 mm
[0020] In the aforementioned three-point bending test, the breaking point (ε f , σ f ) is the maximum stress (σ f ) among the values measured at 0.01-second intervals from the start of the test until fracture, and the strain (ε f ) corresponding thereto.
[0021] The "deformation elastic modulus" (hereinafter also referred to as "Δσ / Δε") refers to the value of the differential coefficient by difference approximation obtained by substituting two adjacent points (ε f , σ f ) of the coordinate value group (ε k , σ k ) (k=1,2,3,···,n) extracted at acquisition time intervals of 0.5 seconds so as to include the coordinate values of the breaking point, from the σ-ε diagram sampled at the aforementioned acquisition interval of 0.01 seconds, into the following equation (3). k-1 , σ k-1 ), (ε k , σ k ) Δσ k / Δε k =(σk -σ k-1 ) / (ε k -ε k-1 ) (3)
[0022] The origin of ε (ε=0) in the Δσ / Δε-ε diagram obtained from equation (3) should be the strain value corresponding to the value less than 0.2 GPa at which the deformation modulus value increases sharply with increasing strain. Therefore, the strain values thereafter should be corrected by subtracting the strain set at the origin.
[0023] Deformation modulus of the fracture point (Δσ f / Δε f ) is the fracture point (ε f ,σ f ) and (ε) 0.5 seconds before reaching the fracture point f-1 ,σ f-1 You can find the answer by substituting ) into equation (4) below. Δσ f / Δε f =(σ f -σ f-1 ) / (ε f -ε f-1 ) (4)
[0024] A "bending point" is a point in the Δσ / Δε-ε diagram where the slope α of the line approximated by the linear relationship in equation (5) below actually changes. Δσ / Δε=αε+β (5)
[0025] In equation (5), α(GPa) and β(GPa) are values obtained by the least squares method.
[0026] Strain at the inflection point (ε b The value of ) is when the strain is 0.0026≦ε<ε b In this case, equation (5) is applied to the plot of the region that can be approximated by a straight line, and the slope α1 and intercept β1 of the line are obtained by the least squares method, and similarly ε b <ε≦ε f The slope α² and intercept β² of the line can be found within the given range and substituted into equation (6) below. ε b=-(β2-β1) / (α2-α1) (6)
[0027] "Measured density" refers to the ratio of mass to volume measured by mass measurement using the Archimedes method (g / cm³). 3 )
[0028] "Monoclinic ratio," "tetragonal ratio," and "rhombohedral ratio" are the proportions of monoclinic, tetragonal, and rhombohedral zirconia in the crystalline phases of zirconia in the surface layer of a zirconia sintered body. The monoclinic ratio, tetragonal ratio, and rhombohedral ratio can be determined from the following equations (7) to (9) using the X-ray diffraction (hereinafter also referred to as "XRD") profile of the surface of the zirconia sintered body after grinding. f m ={I m (111)+I m (-111)} / {I m (111)+I m (-111) +I t (101)+I r (111)+I r (100)} × 100 (7) f t =I t (101) / {I m (111)+I m (-111)+I t (101) +I r (111)+I r (100)} × 100 (8) f r ={I r (111)+I r (100)} / {I m (111)+I m (-111) +I t (101)+I r (111)+I r (100)} × 100 (9)
[0029] In equations (7) to (9), f m This is the monoclinic ratio (%), ft tetragonality, f r , rhombohedral crystallinity, I m (111) and I m (-111) represents the integral intensity of the diffraction lines of the 111 and -111 reflections of monoclinic zirconia, respectively. I t (101) is the integral intensity of the diffraction line of the 101 reflection of tetragonal zirconia. I r (111) and I r (100) represents the integral intensity of the diffraction lines of the 111 and 100 reflections of rhombohedral zirconia, respectively. That is the case.
[0030] The following conditions can be listed as requirements for measuring XRD profiles.
[0031] Radiation source: CuKα radiation (λ=0.15418nm) Measurement mode: Continuous scan Scan speed: 4° / min Step width: 0.01° Measurement range: 2θ = 26° ~ 33°
[0032] In the XRD profile measurement described above, preferably, the diffraction lines corresponding to each reflection of zirconia are measured as diffraction lines having a peak top at the following 2θ.
[0033] 111 reflection of monoclinic zirconia: 2θ = 31.4 ± 0.2° -111 reflection of monoclinic zirconia: 2θ = 28.2 ± 0.2° 10¹ reflection of tetragonal zirconia: 2θ = 30.2 ± 0.2°
[0034] The 111 and 100 reflection diffraction lines of rhombohedral zirconia are observed to overlap, and the peak top 2θ is 2θ = 29.7 ± 0.2°.
[0035] The integrated intensity of the diffraction line from each reflection can be determined using calculation software (e.g., SmartLab Studio II, manufactured by Rigaku Corporation), by selecting the segmented Pearson VII function as the analytical function and separating the diffraction lines from each reflection to match the measured values.
[0036] "The crystallite size determined from the peak top of the volume-based crystallite size distribution" refers to the crystallite size obtained from the volume-based crystallite size distribution determined from the diffraction lines in the XRD profile obtained by X-ray diffraction measurement, and is the value corresponding to the crystallite size at the peak top of the volume-based crystallite size distribution. "Volume-based crystallite size distribution" refers to the distribution of crystallite sizes shown by a log-normal probability density function curve with a total area of 1, obtained by applying the following equation (10) by the fundamental parameter method (By Robert W. Cheary and Alan Coelho, J. Appl. Cryst. 25, 109-212 (1992)) (hereinafter also referred to as the "FP method") to the XRD profile.
[0037] h(Θ) = ∫[f(Θ-Θ) λ )·g(Θ λ )]dΘ λ (10)
[0038] In equation (10), h(Θ) is the profile function of the measured diffraction line, g(Θ λ ) is the instrument-derived profile function (hereinafter also referred to as the "instrument function"), f(Θ) is the profile function of diffraction lines whose extent originates from crystallite size and lattice strain. f(Θ-Θ λ ) is Θ λ This is the profile function of the diffraction line, which has a maximum at [location]. Θ is expressed as Θ=2θ using the Black angle θ(°), 2θ is the diffraction angle formed by the incident direction and the diffraction direction of the X-rays. Θ λThis value can be obtained by the following equation (11).
[0039] Θ λ = 2sin -1 [λ / (2d)] (11)
[0040] In equation (11), d is the spacing between crystal planes corresponding to diffraction lines (hereinafter also referred to as "interplanar spacing"), λ is the wavelength of the incident X-ray, and when CuKα rays are used as the source, λ is 0.15418 nm.
[0041] The measured diffraction line profile includes the optical elements originating from the XRD instrument. The crystallite size distribution is expressed using equation (10) as the instrument-derived function g(Θ). λ This can be determined by finding h(Θ) from ), fitting it to the profile of the measured diffraction line, and refining the parameters of the profile function.
[0042] The same conditions as described above are used for measuring the XRD profile, and the diffraction lines corresponding to each reflection and their peak top 2θ values are also measured in the same manner.
[0043] The crystallite size distribution of the volume distribution in the XRD profile measurement described above can be determined using calculation software (e.g., SmartLab Studio II, Rigaku Corporation). The parameters of the instrument function in the calculation software consist of the XRD instrument and the sample being measured.
[0044] The following are some of the parameters related to the XRD device. Device model / FP model Optical system: BB Scan: Continuous Equatorial aberration: Planar sample & TDI Axis divergence model: Cheary-Coelho Goniometer radius (mm): 300.0 Focal width (mm): 0.04 Focal length (mm): 8 DS, SS (°): 2 / 3 RS (mm): 0.075 RS length (mm): 20 Incident solar slit (°): 5.00 Light-receiving solar slit (°): 5.00 Off-focal radiation size (mm): 3.000 Off-focal radiation ratio: 0.0400 PSD width: 19.2
[0045] The group of parameters related to the measurement sample includes the substance-specific linear absorption coefficient (cm -1 ), the sample width (W) (mm), sample thickness (H) (mm) and sample length (L) (mm) as the sample sizes.
[0046] The values of the sample width (W), sample thickness (H) and sample length (L) as the sample sizes may be measured using a vernier caliper, for example.
[0047] The substance-specific linear absorption coefficient (hereinafter also referred to as "μ") is a value determined by the following formula (12).
[0048] μ=ρΣW i (μ / ρ) i (12)
[0049] In formula (12), μ is the linear absorption coefficient (cm -1 ), ρ is the actually measured density (g / cm 3 ) of the sintered body, W is the mass ratio, (μ / ρ) is the mass absorption coefficient (cm 2 / g), The subscript i is an element constituting the sintered body, W of element i i may be determined as the ratio of [(number of atoms of i) × (atomic weight of i)] / [formula weight of the compositional formula in the sintered body], Examples of the element i include Zr, Y, O, Al, and Si, and The value of the mass absorption coefficient is (μ / ρ)Zr =139, (μ / ρ) Y =124, (μ / ρ) O =11.5, (μ / ρ) Al =49.6, (μ / ρ) Si =63.7(cm 2 / g) may be mentioned.
[0050] The fitting of diffraction lines in the calculation software may be performed under the following conditions. Regarding the background of the diffraction lines, a plurality of reference points serving as base points may be arbitrarily selected within the 2θ measurement range, and the space between every two adjacent points may be determined by interpolation with a B-spline function.
[0051] Peak shape: FP method FP type: Size & Strain Crystallite size distribution: Log-normal distribution Background type: B-spline Number of points used at endpoints: 3 Background refinement: No refinement Parameter editing: 2θ, integrated intensity, crystallite size, distribution RSD
[0052] The "cumulative distribution" of crystallite sizes refers to the cumulative distribution of crystallite sizes, which is shown as a cumulative distribution function curve of a log-normal distribution with the horizontal axis representing the volume-based crystallite size and the vertical axis representing the cumulative probability of crystallites relative to the crystallite size, by applying the above FP method to the XRD profile. The "cumulative probability of crystallites" refers to the probability of crystallites having a specific size shown as the cumulative distribution function curve. Crystallite size D n The cumulative probability F at (nm) n (D n ) may be obtained by substituting the values of D of the crystallite size distribution determined by the calculation software n (n=1,2,3,…,n) and the probability density f n (D n )(n=1,2,3,…,n) into the following formula (13). The origin (n=1) of the cumulative distribution function curve is D1=0, f1(D1)=f1(0)=0.
[0053] F n (Dn )= ΔD1·f1(D1)+ΔD2·f2(D2)+ΔD3·f3(D3)+… …+ΔD n-1 ·f n-1 (D n-1 )+ΔD n ·f n (D n ) (13)
[0054] In equation (12), ΔD n is ΔD n =D n+1 -D n (n=1,2,3,…,n)
[0055] Integrating the cumulative distribution function curve of a log-normal distribution over its entire domain yields a theoretical cumulative probability of 1.
[0056] Crystallite size group [D] determined by calculation software n If, for example, a certain value α(nm) does not exist in the group (n=1,2,3,…,n), the cumulative probability F(α) is the closest D to α(nm) in the crystallite size group. n-1 <α <D n D that satisfies n-1 and D n Extract the F values corresponding to these values. n-1 (D n-1 ) and F n (D n The values of ) can be found using equation (13) and then substituted into equation (14) below.
[0057] F(α) = {[F n (D n )-F n-1 (D n-1 )] / [D n -D n-1 ]}·(α-D n-1 )+F n-1 (D n-1 ) (14)
[0058] The thickness of the surface layer corresponds to the penetration depth of the incident X-rays and can be calculated from the following equation (15).
[0059] H=-(5000 / μ){ln(I / I0)}sinθ (15)
[0060] In equation (15), H is the thickness of the surface layer (μm), μ is the linear absorption coefficient (cm -1 ), I is the intensity of diffracted X-rays (cps), I0 is the intensity (cps) of the incident X-rays. θ is the Black angle (°) of the reflection, which corresponds to the diffraction plane. That is the case.
[0061] μ is a value obtained by equation (12) above.
[0062] The value of H at which the intensity ratio of diffracted X-rays to incident X-rays (I / I0) is 1 / 100 is defined as the thickness of the surface layer (hereinafter referred to as "H"). 1 / 100 It is also called ). Using the value of the Black angle of reflection (θ=15.1°) corresponding to the reflection of tetragonal zirconia 111, H 1 / 100 We just need to find that.
[0063] The test specimens used for the XRD measurement described above are zirconia sintered bodies that have been ground by attaching a #200 grit diamond wheel to a surface grinding machine to remove the surface after sintering, resulting in a surface roughness Ra (hereinafter also referred to as "arithmetic mean roughness") of the measurement surface of 0.05 μm or more and 0.4 μm or less.
[0064] The "crystalline phase" in powders can be identified by XRD measurement. The conditions for XRD measurement are the same as those for the XRD pattern measurement described above, except that the measurement range is 2θ = 20° to 37° and the step size is 0.02°.
[0065] In the XRD measurement described above, the diffraction lines of each reflection of zirconia are preferably measured as diffraction lines having a peak top at the following 2θ.
[0066] 111 reflection of monoclinic zirconia: 2θ = 31 ± 0.5° -111 reflection of monoclinic zirconia: 2θ = 28 ± 0.5° 10¹ reflection of tetragonal zirconia: 2θ = 30 ± 0.5° The diffraction lines corresponding to the 011 and 110 reflections of monoclinic zirconia were measured overlappingly, and the 2θ of their peak tops is 2θ = 24 ± 0.5°.
[0067] The diffraction lines corresponding to the 002 and 020 reflections of monoclinic zirconia were measured overlappingly, and the 2θ of their peak tops is 2θ = 34 ± 0.5°.
[0068] The diffraction lines corresponding to the 200 and -102 reflections of monoclinic zirconia were measured overlappingly, and the 2θ of their peak tops is 2θ = 35 ± 0.5°.
[0069] The "monoclinic ratio" and "tetragonal ratio" of the powder represent the proportion of monoclinic zirconia and tetragonal zirconia in the zirconia crystal phase. Using an XRD profile, the monoclinic ratio and tetragonal ratio can be determined from the following equations (16) and (17).
[0070] f m ={I m (111)+I m (-111)} / {I m (111) +I m (-111)+I t (101)} × 100 (16) f t =I t (101) / {I m (111)+I m (-111) +I t (101)} × 100 (17)
[0071] In equations (16) and (17), f m This is the monoclinic ratio (%), f t This is the tetragonal ratio (%). That is the case.
[0072] "Cryslite size of monoclinic zirconia" (hereinafter, "D m ) and "crystallite size of tetragonal zirconia" (hereinafter referred to as "D t It is also called ). ) is a value obtained from the XRD profile of the powder using the following equations (18) and (19).
[0073] D m =λ / (βcosθ m ) (18) D t =λ / (βcosθ t ) (19)
[0074] In equations (18) and (19), D m This is the crystallite size (nm) of monoclinic zirconia. D t This is the crystallite size (nm) of tetragonal zirconia. λ is the wavelength (nm) of the radiation source used in the XRD measurement. β is the integrated width (°) after correcting for mechanical spreading using silicon (99.99% purity, manufactured by High Purity Chemical Laboratory). θ m and θ t These represent the black angle (°) of monoclinic zirconia with a reflection of -111 degrees, and tetragonal zirconia with a reflection of 101 degrees, respectively. That is the case.
[0075] When using CuKα radiation as the source for XRD measurements, λ is 0.15418 nm.
[0076] The "BET specific surface area" is a value determined by the BET method at one point, in accordance with JIS R 1626-1996, with nitrogen (N2) as the adsorbent.
[0077] [Zirconia sintered body] This embodiment provides a zirconia sintered body containing a stabilizing element (hereinafter also referred to as "the sintered body of this embodiment") which includes one or more stabilizing elements selected from the group consisting of yttrium, calcium, magnesium, and cerium, whose surface crystal phase includes at least monoclinic and tetragonal crystals, and whose deformation modulus at the fracture point in the deformation modulus (Δσ / Δε)-ε diagram determined from the stress (σ)-strain (ε) relationship obtained by a three-point bending test is 130 GPa or less. This results in a zirconia sintered body with a low deformation modulus, a so-called low rigidity, and flexibility.
[0078] The sintered body of this embodiment is a zirconia sintered body having zirconia as its main phase, and more particularly, a sintered body having zirconia as its main phase stabilized with one or more stabilizing elements selected from the group consisting of yttrium, calcium, magnesium, and cerium (hereinafter also simply referred to as "stabilizing elements"). Therefore, the sintered body of this embodiment may be a sintered body made of zirconia stabilized with stabilizing elements.
[0079] A zirconia sintered body stabilized with a stabilizing element is zirconia in which the crystalline phase is stabilized by the solid solution of the element in question into zirconia (ZrO2).
[0080] In this embodiment, the content of the stabilizing element is the molar ratio [mol%] of the stabilizing element converted to oxide relative to the total amount of zirconia (ZrO2) and the stabilizing element converted to oxide.
[0081] The sintered body of this embodiment has a yttrium content (hereinafter also referred to as "yttrium content") of 2.0 mol% or less when converted to Y2O3, a calcium content (hereinafter also referred to as "calcium content") of 6.0 mol% or less when converted to CaO, a magnesium content (hereinafter also referred to as "magnesium content") of 6.0 mol% or less when converted to MgO, and / or a cerium content (hereinafter also referred to as "cerium content") of 8.0 mol% or less when converted to CeO2. If the content of such stabilizing elements is exceeded, the zirconia sintered body will have a high deformation modulus, that is, a rigid, brittle body with poor flexibility.
[0082] In order to lower the deformation modulus, it is preferable that the yttrium content is 2.0 mol% or less, 1.8 mol% or less, or 1.5 mol% or less, the calcium content is 6.0 mol% or less, 5.5 mol% or less, or 5.0 mol% or less, the magnesium content is 6.0 mol% or less, 5.4 mol% or less, or 4.5 mol% or less, and / or the cerium content is 8.0 mol% or less, 7.2 mol% or less, or 6.0 mol% or less.
[0083] To increase mechanical strength, it is preferable that the yttrium content is 0.9 mol% or more, 1.0 mol% or more, or 1.1 mol% or more; the calcium content is 3.0 mol% or more, 3.4 mol% or more, or 4.0 mol% or more; the magnesium content is 1.0 mol% or more, 1.2 mol% or more, or 1.4 mol% or more; and / or the cerium content is 4.0 mol% or more, 4.4 mol% or more, or 4.8 mol% or more.
[0084] The stabilizing element is preferably yttrium. In this embodiment, the yttrium content of the sintered body is 0.9 mol% to 2.0 mol%, 1.0 mol% to 1.8 mol%, 1.0 mol% to 1.5 mol%, or 1.1 mol% or more; the calcium content is 3.0 mol% to 6.0 mol%, 3.4 mol% to 5.5 mol%, 3.4 mol% to 5.0 mol%, or 4.0 mol% or more; the magnesium content is 1.0 mol% to 6.0 mol%, 1.2 mol% to 5.4 mol%, 1.2 mol% to 4.5 mol%, or 1.4 mol% or more; and / or the cerium content is 4.0 mol% to 8.0 mol%, 4.4 mol% to 7.2 mol%, 4.4 mol% to 6.0 mol%, or 4.8 mol% or more.
[0085] In the sintered body of this embodiment, the stabilizing elements are solid-dissolved in zirconia. Preferably, the sintered body of this embodiment does not contain any unsolid-dissolved stabilizing elements, that is, all of the stabilizing elements are solid-dissolved in zirconia. However, it is acceptable to include unsolid-dissolved stabilizing elements as long as the effects of the sintered body of this embodiment are achieved. In the sintered body of this embodiment, it can be considered that it does not contain unsolid-dissolved elements if the diffraction lines of the compounds of the stabilizing elements are not observed in its XRD profile.
[0086] The sintered body of this embodiment may contain one or more additive components selected from alumina and silica, and may also contain alumina. The deformation modulus of the sintered body of this embodiment is low without the effect of the additive components. Therefore, the sintered body of this embodiment does not need to contain additive components (the content of additive components may be 0% by mass). However, it may contain additive components as long as it is within the range that the effects of the sintered body of this embodiment are achieved (the content of additive components may be greater than 0% by mass). This allows for the improvement of fracture toughness due to the additive components, in addition to the effects achieved by the sintered body of this embodiment itself.
[0087] In the sintered body of this embodiment, it is preferable that the content of additive components is small. For example, the content of additive components on an oxide basis (hereinafter also referred to as "amount of additive components," and if the additive component is alumina, it is also referred to as "alumina amount," etc.) may be 5.0% by mass or less, 4.0% by mass or less, or 3.0% by mass or less. Furthermore, if the sintered body of this embodiment contains additive components, the amount of additive components may be greater than 0% by mass, 0.1% by mass or more, or 0.3% by mass or more. Examples of the amount of additive components in the sintered body of this embodiment include 0% by mass or more and 5.0% by mass or less, 0% by mass or more and 4.0% by mass or less, or 0% by mass or more and 3.0% by mass or less. Furthermore, the sintered body of this embodiment contains additive components, and the amount of additive components may be greater than 0% by mass and 5.0% by mass or less, 0.1% by mass or more and 4.0% by mass or less, or 0.3% by mass or more and 3.0% by mass or less.
[0088] In this embodiment, the amount of added components is the mass percentage [mass%] of the added components in oxide form relative to the total of zirconia (ZrO2), the stabilizing elements in oxide form, and the added components in oxide form. The oxide equivalents of the added components are Al2O3 for alumina and SiO2 for silica.
[0089] The sintered body of this embodiment is preferably free of impurities, and preferably below the detection limit (for example, 0.1% by mass). For example, the content of phosphorus (P) as an impurity may be 0.1% by mass or less and less than 0.1% by mass, respectively. Also, the content of metal elements other than zirconia, alumina, silica, and stabilizing elements may be less than 0.1% by mass. On the other hand, it may contain unavoidable impurities such as hafnia (HfO2), which is an unavoidable impurity of zirconia. In the calculation of composition-related values such as density in this embodiment, hafnia (HfO2) may be treated as zirconia (ZrO2) in the calculation.
[0090] If the sintered body of this embodiment is, for example, a sintered body of yttrium-stabilized zirconia containing alumina and silica, its composition can be determined as follows.
[0091] Stabilizing element content (yttrium content) ={Y2O3 / (ZrO2+Y2O3)}×100[mol%] Alumina content (amount of alumina) ={Al2O3 / (ZrO2+Y2O3+Al2O3+SiO2)}×100[mass%] Silica content (silica amount) ={SiO2 / (ZrO2+Y2O3+Al2O3+SiO2)}×100[mass%] Content of added ingredients (amount of added ingredients) ={(Al2O3+SiO2) / (ZrO2+Y2O3+Al2O3+SiO2)}×100[mass%]
[0092] The sintered body of this embodiment is a zirconia sintered body in which the surface layer consists of monoclinic and tetragonal crystals, or monoclinic, tetragonal, and rhombohedral crystals. This results in a low deformation modulus. Preferably, the monoclinic content is 16% to 50%, 20% to 48%, or 30% or more, and the preferred sum of the tetragonal content and rhombohedral content is greater than 50% and less than 84%, greater than 48% and less than 80%, or less than 70%. An example of the sintered body of this embodiment is a monoclinic content of 37% to 48%, and a sum of the tetragonal content and rhombohedral content of greater than 52% and less than 63%.
[0093] In this embodiment, it is preferable that the sintered body has a crystallite size of 3 nm or more and 50 nm or less, determined from the peak top of the volume-based crystallite size distribution obtained from the diffraction lines of monoclinic -111 reflection. More preferably, the crystallite size determined from the peak top of the volume-based crystallite size distribution is 5 nm or more and 40 nm or less, and the cumulative probability of crystallites at a crystallite size of 20 nm is 0.1 or more and 0.85 or less.
[0094] The sintered body of this embodiment has a surface layer with a thickness (H 1 / 100 It is preferable that the thickness is 8 μm or more and 11 μm or less.
[0095] Because it tends to have high mechanical strength, it is preferable that the sintered body of this embodiment has a high measured density. The sintered body of this embodiment has a measured density of 5.95 g / cm³ when the stabilizing element is yttrium. 3 More than 6.16g / cm 3 The following conditions must be met: the measured density when the stabilizing element is calcium is 5.90 g / cm³. 3 More than 6.16g / cm 3 The following conditions must be met: the measured density when the stabilizing element is magnesium is 5.87 g / cm³. 3 More than 6.16g / cm 3 The following conditions must be met, and the measured density when the stabilizing element is cerium is 6.18 g / cm³. 3 More than 6.31g / cm 3 The following are some examples:
[0096] If the measured density is within the above range, the interior, excluding the surface layer, may be a zirconia sintered body with tetragonal zirconia as the main phase. Although zirconia is said to have multiple crystalline phases, in this embodiment, the crystalline phase of the zirconia in the interior, excluding the surface layer, can be considered to consist of two crystalline phases: monoclinic zirconia and tetragonal zirconia. "Having tetragonal zirconia as the main phase" means that among the monoclinic zirconia, tetragonal zirconia, and rhombohedral zirconia contained in the zirconia crystalline phase, tetragonal zirconia accounts for the largest proportion of the crystalline phase.
[0097] In this embodiment, the sintered body exhibits a deformation modulus of 130 GPa or less at the fracture point, as shown in the deformation modulus (Δσ / Δε)-ε diagram obtained from the stress (σ)-strain (ε) relationship in a three-point bending test. This results in a flexible zirconia sintered body with low rigidity.
[0098] One possible reason why the sintered body of this embodiment exhibits a good deformation modulus is as follows: Under load-induced stress, the zirconia sintered body experiences maximum compressive stress on the outermost surface on the side where the load is applied, and this compressive stress decreases toward the center of the cross-section, reaching a neutral point where it becomes zero. On the other hand, maximum tensile stress occurs on the outermost surface on the side where the load is not applied, and this tensile stress decreases toward the center of the cross-section, reaching a neutral point where it becomes zero. In particular, at the outermost surface where maximum compressive and tensile stresses occur, the material becomes more susceptible to deformation due to volume changes caused by the crystal transformation of monoclinic and tetragonal crystals, or monoclinic, tetragonal, and rhombohedral crystals, present in the surface layer, as well as the crystal transformation of tetragonal crystals present in the interior excluding the surface layer, which is thought to reduce the deformation modulus. When the deformation modulus satisfies this value, the material becomes more susceptible to deformation as the stress in the direction of the load increases, resulting in a flexible zirconia sintered body with low rigidity.
[0099] The lower limit of the deformation modulus is 20 GPa or more, 40 GPa or more, or 60 GPa or more. The deformation modulus of the sintered body in this embodiment is 20 GPa or more and 130 GPa or less, 40 GPa or more and 110 GPa or less, 60 GPa or more and 90 GPa or less, or 80 GPa or less.
[0100] In this embodiment, it is preferable that the strain at the bending point is within the range of 0.003 or more and less than or equal to the fracture point, and that in the range between the bending point and the fracture point, the deformation modulus and the strain approximate a linear relationship, and that the slope of the linear relationship is -10000 GPa or less.
[0101] The strain at the bending point is greater than 0.0030 at the fracture point (ε fExamples include values of 0.0035 or more and 0.0055 or less. The slope of the linear relationship is the value of α2 obtained from equation (5) above, and the lower limit of this slope (α2) is -30000 GPa or more, -25000 GPa or more, or -23000 GPa or more. In addition, examples of the slope (α2) of the straight line of the sintered body in this embodiment include -30000 GPa or more and -10000 GPa or less, -25000 GPa or more and -13000 GPa or less, and -23000 GPa or more and -15000 GPa or less. The intercept of the linear relationship is the value of β2 obtained from equation (5) above, and an example of this intercept (β2) is 210 GPa or more and 250 GPa or less. In this embodiment, "the deformation modulus and strain approximate a linear relationship" means that the correlation coefficient of the deformation modulus-strain plot is -0.950 or less, and particularly -0.965 or less. Examples of such correlation coefficients include -0.995 to -0.965.
[0102] The sintered body of this embodiment is preferably a zirconia sintered body obtained by pressure sintering, and more preferably a zirconia sintered body obtained by hot hydrostatic pressing (hereinafter also referred to as "HIP") (a so-called HIP-treated body). The HIP-treated body may be a body that has been treated by another sintering method after pressure sintering, for example, atmospheric pressure sintering after pressure sintering, or a body that has been sintered in an oxidizing atmosphere after HIP treatment.
[0103] The shape of the sintered body in this embodiment can be any desired shape, including cubic, rectangular, polygonal, plate-shaped, disc-shaped, columnar, conical, spherical, approximately spherical, and other basic shapes, as well as any shape suitable for various applications.
[0104] The sintered body of this embodiment can be used as a component in applications known for zirconia sintered bodies, for example, as one or more selected from the group consisting of structural materials, biomaterials, and exterior materials, and further as one or more selected from the group consisting of crusher components, precision machine components, optical connector components, decorative components, electronic equipment exterior components, and dental components.
[0105] [Method for manufacturing zirconia sintered bodies] The manufacturing method for the sintered body of this embodiment is arbitrary as long as a zirconia sintered body satisfying the above-described configuration can be obtained. A preferred manufacturing method for the sintered body of this embodiment is one in which the BET specific surface area is 40 m². 2 / g or more 100m 2 A molded body made of zirconia powder containing one or more stabilizing elements selected from the group consisting of yttrium, calcium, magnesium, and cerium, with a measured density of 5.65 g / cm³, was sintered. 3 More than 5.90g / cm 3 A method for producing a zirconia sintered body (hereinafter also referred to as "the manufacturing method of this embodiment") includes obtaining the following preliminary zirconia sintered body and pressurizing the preliminary zirconia sintered body.
[0106] BET specific surface area 40m 2 / g or more 100m 2 A molded body made of zirconia powder containing one or more stabilizing elements selected from the group consisting of yttrium, calcium, magnesium, and cerium, with a measured density of 5.65 g / cm³, was sintered. 3 More than 5.90g / cm 3 To obtain the following pre-sintered zirconia body (hereinafter also referred to as the "pre-sintering process"), a BET specific surface area of 40 m² is required. 2 / g or more 100m 2 A molded article is provided, made from zirconia powder (hereinafter also referred to as "raw material powder") that is less than or equal to / g and contains one or more stabilizing elements selected from the group consisting of yttrium, calcium, magnesium, and cerium.
[0107] It is preferable that the stabilizing elements contained in the raw material powder are solid-dissolved in the zirconia and do not contain any undissolved stabilizing elements, that is, all of the elements are solid-dissolved in the zirconia. However, it is also acceptable to include undissolved stabilizing elements as long as the sintered body of this embodiment can be obtained.
[0108] The content of stabilizing elements in the raw material powder should be the same as the amount of stabilizing elements in the target zirconia sintered body. When the stabilizing element is yttrium, the amount of yttrium may be 0.9 mol% to 2.0 mol%, 1.0 mol% to 1.8 mol%, 1.0 mol% to 1.5 mol%, or 1.1 mol% or more. When the stabilizing element is calcium, the amount of calcium may be 3.0 mol% to 6.0 mol%, 3.4 mol% to 5.5 mol%, or 3.4 mol% to 5.0 mol%. Examples include being % or less, or 4.0 mol% or more. When the stabilizing element is magnesium, the amount of magnesium is 1.0 mol% to 6.0 mol%, 1.2 mol% to 5.4 mol%, 1.2 mol% to 4.5 mol%, or 1.4 mol% or more. When the stabilizing element is cerium, the amount of cerium is 4.0 mol% to 8.0 mol%, 4.4 mol% to 7.2 mol%, 4.4 mol% to 6.0 mol%, or 4.8 mol% or more.
[0109] Depending on the composition of the target zirconia sintered body, the raw material powder may contain additive components (one or more selected from alumina and silica, and more specifically, alumina) (the content of additive components may exceed 0% by mass). Examples of additive component amounts in the raw material powder include 5.0% by mass or less, 4.0% by mass or less, or 3.0% by mass or less. Furthermore, if the raw material powder contains additive components, examples of additive component amounts include exceeding 0% by mass, 0.1% by mass or more, or 0.3% by mass or more. Examples of additive component amounts in the raw material powder include 0% by mass or more and 5.0% by mass or less, 0% by mass or more and 4.0% by mass or less, or 0% by mass or more and 3.0% by mass or less. Furthermore, the raw material powder may contain additive components, and examples of additive component amounts include exceeding 0% by mass and 5.0% by mass or less, 0.1% by mass or more and 4.0% by mass or less, or 0.3% by mass or more and 3.0% by mass or less.
[0110] The BET specific surface area of the raw material powder is 40 m². 2 / g or more, 50m 2 / g or more, or 60m 2 It is preferable that the BET specific surface area is 40 m² or more.2 If the particle size is less than / g, the average primary particle size, as described later, will increase, making it difficult to densify during presintering, and thus making it difficult to obtain the sintered body of this embodiment. To improve moldability, the BET specific surface area is 100m². 2 / g or less or 90ml 2 It is sufficient if it is less than / g, 40m 2 / g or more 100m 2 / g or less, 50m 2 / g or more 100m 2 / g or less, or 60m 2 / g or more 90m 2 One example is that it should be less than or equal to / g.
[0111] The raw material powder may have any size of primary particles as long as it has the BET specific surface area described above. The average primary particle diameter of the raw material powder is preferably 100 nm or more, 150 nm or more, or 160 nm or more. The average primary particle diameter of the raw material powder may be 300 nm or less, 250 nm or less, or 180 nm or less, and is preferably 100 nm to 300 nm, 150 nm to 180 nm, or 160 nm to 180 nm.
[0112] By controlling the average primary particle size, the deformation modulus of the resulting zirconia sintered body can be controlled. That is, by making the average primary particle size of the raw material powder relatively small, the surface layer of the resulting zirconia sintered body becomes monoclinic and tetragonal, or monoclinic, tetragonal, and rhombohedral. Preferably, the monoclinic content can be controlled to be between 16% and 50%, and the sum of the tetragonal and rhombohedral content can be controlled to be greater than 50% and less than 84%.
[0113] The raw material powder has a median diameter (D 50 The midpoint may be 500 nm or less, 400 nm or less, or 300 nm or less, and may also be 50 nm or more, 100 nm or more, 120 nm or more, or 150 nm or more. Furthermore, this median diameter may be 50 nm or more and 500 nm or less, 100 nm or more and 400 nm or less, 120 nm or more and 300 nm or less, or 150 nm or more and 300 nm or less.
[0114] The median diameter is determined by measuring the volume particle size distribution curve of a powder sample using the MT3000II mode of a Microtrac particle size distribution analyzer (product name: MT3000II, manufactured by Microtrac-Bell). 50 ) can be measured. In addition, prior to measurement, the powder sample can be suspended in a 0.2% by mass sodium hexametaphosphate aqueous solution and dispersed for 10 minutes using an ultrasonic homogenizer as a pretreatment.
[0115] The raw material powder is preferably monoclinic or monoclinic-tetragonal mixed phase zirconia, and the crystallite size of the zirconia is monoclinic (D m ) and tetragonal (D t It is preferable that both of the crystallite sizes are 20 nm or less, 15 nm or less, or 10 nm or less. It is thought that the finer the crystallite size of the monoclinic and tetragonal crystals, the more densified the pre-sintering becomes, making it easier for tetragonal crystals to form inside the resulting zirconia sintered body, which in turn makes it more susceptible to deformation and thus lowers the deformation modulus. The smaller the crystallite size of the monoclinic and tetragonal zirconia, the better, but it is preferable that it be 4 nm or more.
[0116] The raw material powder may also be in granular form.
[0117] The raw material powder is preferably a powder obtained by the manufacturing method described later.
[0118] The molded body can be any composition (compacted powder) in which the raw material powder, that is, the powder particles constituting the raw material powder, are aggregated to have a certain shape, and can be any molded body manufactured by any molding method that does not cause changes in the composition of the raw material composition, BET specific surface area, average primary particle diameter, etc. The molding method can be one or more selected from the group consisting of uniaxial press molding, cold isostatic pressing (CIP) molding, slip casting, and injection molding, and more specifically, at least one selected from the group consisting of uniaxial press molding, CIP molding, and injection molding, with uniaxial press molding and CIP molding being preferred.
[0119] When the forming method is uniaxial press forming and CIP forming, it is preferable that the ratio of the uniaxial press forming pressure [MPa] to the CIP forming pressure [MPa] is 0.25 or less, more preferably 0.05 to 0.25, more preferably 0.15 to less than 0.25, and more preferably 0.20 to less than 0.25, and more preferably the CIP forming pressure is 200 MPa or more, and more preferably greater than 250 MPa. The upper limit of the CIP forming pressure can be 1 GPa or less, 500 MPa or less, 350 MPa or less, or 300 MPa or less, and it is preferable that it is 200 MPa to 350 MPa, or greater than 250 MPa and less than or equal to 300 MPa.
[0120] Compared to powders commonly used as raw materials for zirconia sintered bodies, the raw material powder has a higher BET specific surface area. Powders with a high BET specific surface area are difficult to mold even if molded at high pressure. In contrast, the average primary particle size of the raw material powder is controlled to an appropriate size. By controlling the relationship between the pressure of uniaxial press molding and the pressure of CIP molding within this range, the raw material powder can be molded into a compact (molded body) despite its high BET specific surface area.
[0121] While the pressure for uniaxial press forming can be any pressure as long as the above-described relationship is satisfied between the pressure for uniaxial press forming and the pressure for CIP forming, it is preferable that the pressure be 50 MPa or higher, more preferably 65 MPa or higher, and also 90 MPa or lower, or 80 MPa or lower, in order to improve handling after uniaxial press forming. Examples include 50 MPa to 90 MPa or 65 MPa to 80 MPa.
[0122] The molded body is subjected to a pre-sintering process. The sintering in the pre-sintering process should be such that a pre-zirconia sintered body that can be densified in the subsequent pressure sintering is obtained, and atmospheric pressure sintering is preferred. The measured density that can be densified by pressure sintering is 5.65 g / cm³. 3 More than 5.90g / cm 3 The following are some examples:
[0123] In this embodiment, "atmospheric pressure sintering" refers to a method of sintering a material (such as a molded body or calcined body) by heating it at a temperature above the temperature at which zirconia sintering progresses (hereinafter also referred to as the "sintering temperature") without applying any external force to the material during sintering. Preferred conditions for atmospheric pressure sintering include the following:
[0124] Atmosphere: Oxidizing atmosphere, Preferably an atmospheric environment Holding temperature: 1100°C or higher or 1200°C or higher, 1300℃ or below or 1250℃ or below
[0125] The pre-sintering time can be adjusted as appropriate depending on the size and quantity of the molded body to be pre-sintered, as well as the sintering furnace used. For example, it can be between 0.5 hours and 24 hours, or between 1 hour and 15 hours.
[0126] The sintered body of this embodiment can be manufactured by pressurizing and sintering a pre-sintered zirconia body (hereinafter also referred to as the "pressurized sintering process").
[0127] Pressure sintering includes at least one of hot press (HP) treatment and hot isostatic press (HIP) treatment, with HIP treatment being preferred.
[0128] The following conditions can be cited as requirements for pressure sintering.
[0129] Atmosphere: Relaxing atmosphere, Preferably, at least one of a nitrogen atmosphere and an argon atmosphere. Comfortable argon atmosphere Holding pressure: 50 MPa or more or 100 MPa or more, 500 MPa or less or 200 MPa or less Holding temperature: 1100°C or higher, 1150°C or higher, or 1230°C or higher, Below 1350℃, below 1300℃, or below 1270℃
[0130] The holding temperature during pressurized sintering is preferably higher than the holding temperature during pre-sintering, and more preferably 50±10°C higher than the holding temperature during pre-sintering.
[0131] The time for pressurized sintering can be adjusted as appropriate depending on the size and quantity of the pre-sintered zirconia body to be subjected to pressurized sintering, as well as the pressurized sintering furnace used. For example, it can be between 0.5 hours and 15 hours, or between 0.5 hours and 5 hours.
[0132] [Method for producing raw material powder] The raw material powder used in the pre-sintering process is a powder for zirconia sintered bodies, and is a powder for producing molded bodies, a powder for producing calcined bodies, or a powder for producing zirconia sintered bodies, and is a powder that becomes one or more precursors selected from the group consisting of molded bodies, calcined bodies, and zirconia sintered bodies. A preferred method for producing it is a method (hereinafter also referred to as "this powder production method") that includes an alcohol treatment step to obtain a compound (hereinafter also referred to as "raw material compound") obtained by heat treatment of a composition having an average sol particle size of 150 nm to 400 nm and containing hydrated zirconia powder and one stabilizing element source selected from the group consisting of yttrium, calcium, magnesium, and cerium, and then an alcohol treatment step to obtain a powder precursor, and a drying step to dry the powder precursor in a reduced pressure atmosphere.
[0133] The composition is heat-treated at temperatures between 450°C and 650°C, and more specifically, between 480°C and 600°C. Heating at temperatures above 450°C yields a powder that is easily densified by pre-sintering. On the other hand, heat-treating at temperatures below 650°C yields a powder that is easily dispersed by the alcohol treatment described later. The heat treatment time varies depending on the heat treatment temperature, but examples include 30 minutes to 2 hours.
[0134] The atmosphere for heat treatment is arbitrary and can be selected from the group consisting of an oxidizing atmosphere, a reducing atmosphere, an inert atmosphere, and a vacuum atmosphere. An oxidizing atmosphere is preferred, and an atmospheric atmosphere is more preferred.
[0135] A powder precursor is obtained by going through an alcohol treatment process. In the raw material compound subjected to the alcohol treatment process, the stabilizing element source may be any compound of a stabilizing element, and one or more selected from the group of chlorides, hydroxides, and oxides are examples, with at least one of chlorides and hydroxides, and more preferably chloride. For example, the yttrium source may be any compound of yttrium, and one or more selected from the group of yttrium chloride, yttrium hydroxide, and yttrium oxide (yttria), with at least one of yttrium chloride and yttrium hydroxide, and more preferably yttrium chloride.
[0136] The raw material compound used in the alcohol treatment process consists of zirconia particles in which stabilizing elements are solid-solved.
[0137] The zirconia sol preferably contains zirconia that includes monoclinic zirconia, and more preferably contains zirconia made of crystalline zirconia (hereinafter also referred to as "crystalline zirconia sol"), and more preferably contains crystalline zirconia in which the main phase is monoclinic zirconia.
[0138] The zirconia sol has an average sol particle size of 150 nm to 400 nm, preferably 200 nm to 300 nm. Such a zirconia sol can be manufactured, for example, by the method disclosed in Japanese Patent Application Publication No. 2022-008052.
[0139] The content of stabilizing elements in terms of oxides should be the same as the amount of stabilizing elements in the target raw material powder. Examples include: yttrium content of 0.9 mol% to 2.0 mol%, 1.0 mol% to 1.8 mol%, 1.0 mol% to 1.5 mol%, or 1.1 mol% or more; calcium content of 3.0 mol% to 6.0 mol%, 3.4 mol% to 5.5 mol%, 3.4 mol% to 5.0 mol%, or 4.0 mol% or more; magnesium content of 1.0 mol% to 6.0 mol%, 1.2 mol% to 5.4 mol%, 1.2 mol% to 4.5 mol%, or 1.4 mol% or more; and cerium content of 4.0 mol% to 8.0 mol%, 4.4 mol% to 7.2 mol%, 4.4 mol% to 6.0 mol%, or 4.8 mol% or more.
[0140] Depending on the composition of the target raw material powder, the raw material powder may contain additive components (one or more selected from alumina and silica, and more specifically, alumina) (the content of additive components may exceed 0% by mass). Examples of additive component amounts in the raw material powder include 5.0% by mass or less, 4.0% by mass or less, or 3.0% by mass or less. Furthermore, if the raw material powder contains additive components, examples of additive component amounts include exceeding 0% by mass, 0.1% by mass or more, or 0.3% by mass or more. Examples of additive component amounts in the raw material powder include 0% by mass or more and 5.0% by mass or less, 0% by mass or more and 4.0% by mass or less, or 0% by mass or more and 3.0% by mass or less. Furthermore, if the raw material powder contains additive components, examples of additive component amounts include exceeding 0% by mass and 5.0% by mass or less, 0.1% by mass or more and 4.0% by mass or less, or 0.3% by mass or more and 1.5% by mass or less.
[0141] In the alcohol treatment process, the raw material compound is treated with alcohol. In this embodiment, "alcohol treatment" refers to a process in which the raw material compound is brought into contact with a wet atmosphere using alcohol as a solvent. It is believed that by treating the raw material compound with alcohol, the surface of the raw material compound, particularly the zirconia contained in the raw material compound, is modified. As a result, the zirconia in the raw material compound becomes moderately and slowly aggregated, and after the subsequent drying process, it is believed that a raw material powder with high moldability despite having a high BET specific surface area can be obtained.
[0142] The alcohol can be one or more selected from methanol, ethanol, butanol, and octanol, and is preferably at least one of methanol and ethanol, and more preferably ethanol.
[0143] The method of alcohol treatment is arbitrary as long as it does not subject the raw material compound to excessive stress and the raw material compound and alcohol are in sufficient contact. For example, the alcohol and raw material compound can be mixed to form a slurry and stirred. Alternatively, the alcohol treatment method may also include a method to remove slow aggregation of the raw material compound in addition to contact between the alcohol and the raw material compound. Examples of specific treatment methods include mortar mixing and ball mill mixing, with ball mill mixing being the preferred method.
[0144] Examples of slurries used in alcohol treatment include slurries in which the mass ratio of the raw material compound to the total slurry mass is 30% by mass or more and 50% by mass or less.
[0145] In the drying process, the powder precursor is dried under reduced pressure. The powder precursor obtained after the drying process has a high BET specific surface area, making it prone to forming strong aggregates during drying. However, drying under reduced pressure suppresses the aggregation of the powder precursor while drying progresses, resulting in a more moldable raw material powder.
[0146] A reduced-pressure atmosphere is an atmosphere with lower pressure than the atmospheric atmosphere, and may be 0.1 MPa or less, 500 hPa or less, or 200 hPa or less. To achieve an appropriate drying rate, the reduced-pressure atmosphere is preferably 50 hPa or higher or 100 hPa or higher, and preferred reduced-pressure atmospheres include 50 hPa to 0.1 MPa or 100 hPa to 200 hPa.
[0147] The drying temperature should be a temperature at which rapid evaporation of the solvent, ethanol, is unlikely to occur, and is preferably 80°C or lower, 60°C or lower, or 50°C or lower. The drying temperature should be 20°C or higher or 30°C or higher, and may also be 20°C to 60°C or 30°C to 50°C.
[0148] To improve the handling properties of the raw material powder, this powder manufacturing method may include a granulation step in which the raw material powder obtained by the drying step is granulated.
[0149] Granulation can be carried out by any method, but one method is spray granulation of a slurry obtained by mixing powder and a solvent. The solvent is at least one of water and alcohol. The granulated powder (hereinafter also referred to as "powder granules") has an average granule size of 30 μm or more and 80 μm or less. [Examples]
[0150] The present disclosure will be described below using examples. However, the present disclosure is not limited to these examples.
[0151] (Average sol particle size) The average particle size of the zirconia sol was measured using a dynamic light scattering particle size distribution analyzer (instrument name: NANOTRAC WAVE II, manufactured by Microtrac). As a sample pretreatment, the hydrated zirconia sol-containing solution was suspended in pure water, and the suspension was dispersed for 1 minute using an ultrasonic cleaner.
[0152] (Phase fraction and crystallite size of powder) A standard X-ray diffractometer (product name: SmartLab, manufactured by Rigaku Corporation) was used to obtain XRD profiles of powder samples. The XRD measurement conditions were as follows:
[0153] Radiation source: CuKα radiation (λ=0.15418nm) Measurement mode: Continuous scan Scan speed: 4° / min Step width: 0.02° Measurement range: 2θ = 20° to 37°
[0154] Using the obtained XRD profile and calculation software (product name: SmartLab StudioII, manufactured by Rigaku Corporation), the monoclinic fraction (f) is calculated using equations (16) to (19). m ), crystallite size (D) of monoclinic zirconia m ), tetragonal fraction (f t ) and the crystallite size (D) of tetragonal zirconia t The diffraction line background was determined by selecting 20° and 37° and interpolating between these two points using a B-spline function.
[0155] (BET specific surface area) The BET specific surface area of powder samples was measured using a general-purpose fluidized bed specific surface area (TriStar II, manufactured by Micromeritics) in accordance with JIS R 1626-1996. Nitrogen gas was used as the adsorption gas. Prior to measurement, the powder samples were pre-treated by degassing in an air atmosphere at 250°C for 30 minutes.
[0156] (particle size distribution) The volume particle size distribution curve of a powder sample is measured using the MT3000II mode of the Microtrac particle size analyzer (product name: MT3000II, manufactured by Microtrac-Bell). The median diameter (D 50 The following measurements were taken. Prior to the measurements, the powder sample was suspended in a 0.2% by mass aqueous solution of sodium hexametaphosphate and dispersed for 10 minutes using an ultrasonic homogenizer as a pretreatment.
[0157] (Measured density of zirconia sintered body) The actual density of zirconia sintered body samples was measured using the Archimedes method. Prior to the measurement, the mass of the dried zirconia sintered body was measured, and then the zirconia sintered body was placed in water and boiled for 1 hour as a pretreatment.
[0158] (Crystalline fraction of zirconia sintered body) XRD measurements of the zirconia sintered body sample were performed under the same conditions as the powder sample, except that the measurement range of 2θ was set to 26°~33° and the step size to 0.01°. Using the obtained XRD profile and calculation software (software name: SmartLab StudioII, Rigaku Corporation), the tetragonal crystal structure (f) was determined using equations (7)~(9). t ), monoclinic (f m ) and rhombohedral crystallinity (f r The diffraction line background was determined by selecting 26° and 33° and interpolating between these two points using a B-spline function.
[0159] In the XRD profiles of Examples 1 to 5, the diffraction intensities of the rhombohedral crystal's 111 and 100 reflections were weak and observed as a shoulder peak shape next to the tetragonal crystal's 111 reflection. Therefore, the rhombohedral crystal's 111 and 100 reflections were treated as a single diffraction line, and the calculation was performed assuming that the full width at half maximum of that diffraction line was equal to the full width at half maximum of the monoclinic crystal's -111 reflection, thereby determining the integral intensity of the rhombohedral crystal. For Comparative Example 1, the calculation was performed by treating the rhombohedral crystal's 111 and 100 reflections as a single diffraction line, and the integral intensity was determined.
[0160] Furthermore, under these yttrium content and sintering conditions, a portion of the tetragonal crystal undergoes a phase transformation to a cubic crystal during the sintering process. However, since the cubic 111 reflection and the tetragonal 101 reflection overlap, the cubic 111 reflection and the tetragonal 101 reflection were calculated as a single diffraction line, and the cubic crystal was treated as a tetragonal crystal.
[0161] For XRD measurement, a surface grinder fitted with a #200 grit diamond wheel was used to grind the sintered surface, and a zirconia sintered body sample with a surface roughness (Ra) of 0.05 μm or more and 0.4 μm or less after the grinding treatment was used.
[0162] (Surface Roughness of Zirconia Sintered Body) The surface roughness (Ra) of the ground zirconia sintered body was measured using a laser microscope (trade name: VK-9500 / VK-9510, manufactured by Keyence Corporation), and Ra was obtained as the arithmetic mean roughness. The conditions for surface roughness measurement are as follows.
[0163] Lens Magnification: ×150 Z-direction Step: 0.01 μm Prior to measurement, the sintered body sample was immersed in an ethanol solution and then subjected to ultrasonic cleaning treatment as a pretreatment.
[0164] (Crystallite Size Distribution) The XRD profile was measured under the same conditions as the aforementioned zirconia sintered body sample. Using the obtained XRD profile and calculation software (product name: SmartLab StudioII, manufactured by Rigaku Corporation), analysis was performed under the aforementioned apparatus function parameter group and diffraction line fitting conditions, to determine the crystallite size value at the peak top in the volume-based crystallite size distribution. The 111 and 100 reflections of the rhombohedral crystal were treated as a single diffraction line, and for the background of the diffraction line, 26° and 33° were selected, and the interval between these two points was determined by interpolation with a B-spline function. Here, the linear absorption coefficient, which is a parameter of the apparatus function, was obtained from Equation (12), and the values of W, H and D of the sample size were values measured with a vernier caliper. The value of the mass absorption coefficient is (μ / ρ) Zr =139, (μ / ρ) Y =124, (μ / ρ) O =11.5, (μ / ρ) Al =49.6, (μ / ρ) Si =63.7 (cm 2 / g) was used. Table 1 shows the linear absorption coefficients and the values of W, H and L of the sample size for the Examples and Comparative Examples.
[0165]
Table 1
[0166] The value of cumulative probability F(20) at a crystallite size α=20 nm was determined from Equations (13) and (14) using the crystallite size and crystallite probability density values obtained from the crystallite size distribution.
[0167] (Thickness of Surface Layer) The thickness (H of the surface layer of the zirconia sintered body sample 1 / 100 ) was determined by the aforementioned Equation (15) using the values of I / I0=1 / 100, θ=15.1°, and the linear absorption coefficient values in Table 1.
[0168] (Three-Point Bending Test) The load (P)-deflection (s) curve of the zirconia sintered body sample was measured by a three-point bending test in accordance with JIS R1601. A general autograph (trade name: AGS-10kNX, manufactured by Shimadzu Corporation, analysis software: TRAPEZIUM LITE X, manufactured by Shimadzu Corporation) was used to obtain the load (P)-deflection (s) curve of the test piece. The conditions for autograph measurement and test piece size are as follows.
[0169] ·Autograph Distance between supporting points: 30±0.1 mm Crosshead speed: 0.5 mm / min Sampling acquisition interval: 0.01 seconds ·Test piece size Width of test piece: 4.00±0.1 mm Thickness of test piece: 3.00±0.1 mm Length of test piece: 36 mm or more and less than 45 mm
[0170] Strain at breaking point (ε f ), deformation elastic modulus at breaking point (Δσ f / Δε f ), strain at inflection point (ε b ), constants A1 and B1 of the linear approximation line (Δσ / Δε=A1ε+B1) in 0.0026≦ε<ε b , εb <ε≦ε f The constants A2 and B2 of the linear approximation line (Δσ / Δε=A2ε+B2) were determined from equations (3) to (6) above, and the average values of five measurements were used as these values.
[0171] (Bending strength) The bending strength of the zirconia sintered body sample was measured using a three-point bending test in accordance with JIS R1601. The measurement was performed using a columnar zirconia sintered body sample with a width of 4 mm and a thickness of 3 mm, with a support distance of 30 mm, and the average value of 10 measurements was used as the bending strength.
[0172] <Example 1> To an aqueous solution of hydrated zirconia powder with an average sol particle size of 213 nm, yttrium chloride hexahydrate was added to achieve a yttrium content of 1.3 mol%. While stirring the aqueous solution after the addition, a 1 mol / L aqueous ammonia solution was added at a rate of 0.8 kg / h to adjust the pH to 9.5 ± 0.5, yielding a precipitate consisting of hydrated zirconia and yttrium hydroxide. The obtained precipitate was washed with 7 L of 0.1 mol / L aqueous ammonia, then washed with 2 L of pure water, and dried in an air atmosphere at 120°C to obtain the composition. The obtained composition was treated in an air atmosphere at a heating temperature of 530°C for 2 hours to obtain the starting compound.
[0173] The raw material compound was mixed with ethanol to form a slurry, which was then subjected to ball milling using zirconia balls. Finally, it was dried using a rotary evaporator under reduced pressure of 150 hPa and at a temperature of 40°C to obtain a powder consisting of yttrium-containing zirconia with an yttria content of 1.3 mol%, which was used as the powder for this example.
[0174] The powder of this embodiment was uniaxially press-molded at a pressure of 70 MPa, and then subjected to CIP treatment at a pressure of 294 MPa to obtain a molded body (compacted powder) (molding pressure ratio: 0.24). The obtained molded body was subjected to atmospheric pressure sintering in an air atmosphere at a holding temperature of 1240°C for a holding time of 8 hours to obtain a preliminary zirconia sintered body. The preliminary zirconia sintered body was subjected to HIP treatment in an argon atmosphere at a processing pressure of 150 MPa, a holding temperature of 1250°C for a holding time of 1 hour to obtain the zirconia sintered body (HIP-treated body) of this embodiment.
[0175] <Example 2> Except for adding 0.5% by mass of alumina sol (in terms of Al2O3) to an aqueous solution of hydrated zirconia powder, a powder consisting of yttrium-containing zirconia with an alumina content of 0.5% by mass and an yttria content of 1.3 mol% was obtained in the same manner as in Example 1, and this was used as the powder for this example.
[0176] A zirconia sintered body was obtained in the same manner as in Example 1, except that the powder in question was used and the pre-sintering holding time was set to 2 hours.
[0177] <Example 3> Except for adding 1% by mass of alumina sol (in terms of Al2O3) to an aqueous solution of hydrated zirconia powder, a powder consisting of yttrium-containing zirconia with an alumina content of 1% by mass, a silica content of 0.03% by mass, and an yttria content of 1.3 mol% was obtained using the same method as in Example 1, and this was used as the powder for this example.
[0178] A zirconia sintered body was obtained in the same manner as in Example 1, except that the powder in question was used and the pre-sintering holding time was set to 4 hours.
[0179] <Example 4> To a hydrated zirconia sol aqueous solution, yttrium chloride hexahydrate was added so that the yttrium content was 1.2 mol%, and alumina sol and silica sol in an amount of 0.03 mass% in terms of SiO₂ were added so that the alumina content was 1.5 mass%. Except for the above operations, the same method as in Example 1 was carried out to obtain a powder composed of yttrium-containing zirconia with an alumina content of 1.5 mass% and a yttrium content of 1.2 mol%, which was used as the powder of this Example.
[0180] A zirconia sintered body was obtained in the same manner as in Example 1, except that the above powder was used and the holding time of pre-sintering was set to 1 hour.
[0181] <Example 5> To a hydrated zirconia sol aqueous solution, yttrium chloride hexahydrate was added so that the yttrium content was 1.1 mol%, and alumina sol was added so that the alumina content was 3 mass%. Except for the above operations, the same method as in Example 1 was carried out to obtain a powder composed of yttrium-containing zirconia with an alumina content of 3 mass% and a yttrium content of 1.1 mol%, which was used as the powder of this Example.
[0182] A zirconia sintered body was obtained in the same manner as in Example 1, except that the above powder was used and the holding time of pre-sintering was set to 1.5 hours.
[0183] <Comparative Example 1> Yttrium chloride hexahydrate was added to an aqueous solution of hydrated zirconia powder having an average sol particle size of 76 nm so that the yttrium content was 3.0 mol%. While stirring this solution, a 1 mol / L ammonia aqueous solution was added at a rate of 0.8 kg / h so that the pH reached 9.5±0.5, to obtain a precipitate composed of hydrated zirconia and yttrium hydroxide. The obtained precipitate was washed with 2 L of pure water and dried at 120°C in an air atmosphere to obtain a composition. The obtained composition was treated in an air atmosphere at a heating temperature of 950°C for 2 hours to obtain a raw material compound.
[0184] The raw material compound was mixed with pure water to form a slurry, which was then ball-milled using zirconia balls and dried in the air at 120°C to obtain a powder consisting of yttrium-containing zirconia with an yttria content of 3.0 mol%, which was used as the powder for this comparative example.
[0185] The powder of this comparative example was subjected to uniaxial press molding at a pressure of 70 MPa to obtain a molded body (compacted powder). The obtained molded body was subjected to atmospheric pressure sintering at a holding temperature of 1500°C for a holding time of 2 hours to obtain the zirconia sintered body of this comparative example.
[0186] The results of the examples and comparative examples are shown in Tables 2 and 3, the deformation modulus-strain diagrams for Example 1 and Comparative Example 1 are shown in Figure 1, the linear approximation line (Δσ / Δε=αε+β) of the deformation modulus-strain diagrams determined by the least squares method is shown in Figure 2, and the volume-based (a) crystallite size distribution and (b) cumulative crystallite size distribution obtained from the diffraction lines of monoclinic -111 reflection for Example 1 and Comparative Example 1 are shown in Figure 3.
[0187] [Table 2]
[0188] [Table 3]
[0189] The zirconia sintered body of the example has a deformation modulus (Δσ) at the fracture point. f / Δε f The rigidity was found to be less than 130 GPa, indicating that it is a flexible zirconia ceramic with low rigidity. Furthermore, ε b <ε≦ε f Within this range, Δσ / Δε and ε exhibit a linear relationship with a correlation coefficient between 0.968 and 0.994, and the slope (α2) is less than or equal to -10000 GPa. Therefore, it can be seen that beyond the inflection point, the deformation modulus decreases with increasing stress, meaning that the zirconia ceramic becomes more flexible.
Claims
1. It contains one or more stabilizing elements selected from the group consisting of yttrium, calcium, magnesium, and cerium. The surface crystalline phase includes at least monoclinic and tetragonal phases, and The deformation modulus at the fracture point, as determined from the stress (σ)-strain (ε) relationship obtained from a three-point bending test, is 130 GPa or less, as shown in the deformation modulus (Δσ / Δε)-ε diagram. Zirconia sintered body.
2. The zirconia sintered body according to claim 1, wherein the crystalline phase of the surface includes rhombohedral crystals.
3. When converted to oxides, the yttrium content is 0.9 mol% or more and 2.0 mol% or less, the calcium content is 3.0 mol% or more and 6.0 mol% or less, the magnesium content is 1.0 mol% or more and 6.0 mol% or less, and / or the cerium content is 4.0 mol% or more and 8.0 mol% or less, and The monoclinic ratio of the surface is 16% or more and 50% or less. A zirconia sintered body according to claim 1 or 2.
4. The strain at the bending point is 0.003 or more, and less than or equal to the fracture point. The deformation modulus and strain at a point where the strain is above the bending point and below the fracture point have a linear relationship, and furthermore, The slope of the line is -10000 GPa or less. A zirconia sintered body according to claim 1 or 2.
5. A zirconia sintered body according to claim 1 or 2, comprising at least one additive component of alumina and silica.
6. The zirconia sintered body according to claim 5, wherein the content of the additive component is 5.0% by mass or less.
7. BET specific surface area is 40 m² 2 / g or more 100m 2 A molded body made of zirconia powder containing one or more stabilizing elements selected from the group consisting of yttrium, calcium, magnesium, and cerium, with a measured density of 5.65 g / cm³, was sintered. 3 5.90g / cm or more 3 To obtain the following preliminary zirconia sintered bodies, and, The aforementioned pre-sintered zirconia body is pressure-sintered. A method for producing a zirconia sintered body according to claim 1 or 2, including the method described above.
8. A member comprising a zirconia sintered body according to claim 1 or 2.
Citation Information
Patent Citations
Combined plate, and production method thereof
JP2014113726A